Sport Activities as a Vehicle for HIV/ AIDS Prevention in Trinidad and Tobago: Organizer’s Perspectives - Ruheena Sangrar; Shelley Vaisberg; Janet Njelesani; Helene Polatajko (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Various sporting activities are being used as vehicles for HIV/AIDS education and prevention within the field of sport-for-development (SFD). Kicking AIDS Out! is one SFD program that aims to promote protective attitudes regarding HIV/AIDS amongst youth. This study explored organizers’ perspectives of the use of sporting activities in the Kicking AIDS Out! program in Trinidad and Tobago. Qualitative case study methodology was used to examine the case. Data was generated through semi-structured interviews with seven organizers who were Kicking AIDS Out! staff or volunteer members. Thematic analysis guided data analysis. Generated themes include: Sport to Draw, There’s Something for Everyone, the Emotional Wow, and Beyond Sports. These themes illuminate the idea that sport captivates and attracts youth, and illustrate the use of sport activities to promote engagement in the program as they are tailored to the skills and interests of youth. Sport activities may challenge values and beliefs regarding HIV/AIDS and may promote engagement in new roles, such as those as advocate or caregiver for individuals with HIV/AIDS, and engagement in healthy lifestyle behaviours, such as safe sexual encounters. The findings of this study offer an opportunity for HIV/AIDS prevention programs to consider their use of sporting activities in a manner that achieves these SFD characteristics.
Keywords: Sport-for-Development